Isolation and characterization of lignin from rubber wood in ionic liquid medium. - Shamsuri, Ahmad Adlie; Abdullah, Dzulkefly Kuang (Canadian Center of Science and Education, 2010)
In this study, lignin was isolated from rubber wood by means of ionic liquid (1,3-dimethylimidazolium methylsulfate). The optimum parameters to isolate lignin were investigated which include the concentrations of ionic liquid (0.1, 0.2, 0.3, 0.4, 0.5 moles), isolation durations (30, 60, 90, 120, 150 minutes), and isolation temperatures (25, 40, 60, 80, 100°C). The optimum parameters for lignin isolation are 0.5 moles concentration, 120 minutes and 100°C. Lignin could be isolated from rubber wood up to 13.03wt.% by ionic liquid however, in comparison with acid and alkaline isolation, they give better yields than ionic liquid which 22.15wt.% and 1 8.56wt.% of lignin, respectively. Lignin preliminary structures isolated by ionic liquid have been confirmed based on Fourier transform infrared (FTIR) results. From these results, isolated lignin by ionic liquid provides lignin without other related isolative. Apart from that, ionic liquid also could be recycled up to three times compared to acid and alkaline isolation methods.